The Analysis of Factors that Related to Advanced Pentavalent Immunization Status in Sinjai Regency - Indra Dwinata; Dian Pratiwi Ahmad; Dian Sidik Arsyad (Jurnal Berkala Epidemiologi, 2019)
Background: Basic pentavalent immunization coverage in Sinjai Regency in 2017 has reached the target, but the advanced pentavalent immunization rate is still low (52.90%). This condition leads to make a huge gap in toddlers’ immunization status. Purpose: This study aims to determine the factors associated with advanced pentavalent immunization status in the work area of Kampala Health Service Center (PUSKESMAS), Sinjai Regency. Methods: The cross-sectional study was used in this study. The mothers who have the children aged 18-36 months were used as population. About 145 samples were obtained by using simple random sampling technique. The two-way data collection technique, namely primary data obtained through questionnaires and secondary data obtained from the evaluation data of pentavalent immunization at Kampala Health Service Center, Sinjai Regency. Furthermore, chi-square was used for data analysis. Results: Generally, the respondents were 25-29 years old in average (26.90%) and had a high school/ equivalent education degree (53.80%). The respondents’ occupation are mostly housewives (83, 40%). Moreover, the toddlers were 24-29 months-old (46.90%) in average. This study showed that the majority of respondents did not take advanced pentavalent immunization (61.38%). Factors affecting the immunization status of the pentavalent were maternal knowledge (p = 0.03), family support (p= <0.01), and the role of health workers (p= <0.01). Surprisingly, the maternal attitude (p=0.57) and access to immunization services (p=0.17) were not related to advanced pentavalent immunization status. Conclusion: There was a relationship between maternal knowledge, family support, and the role of health workers with advanced pentavalent immunization status